The Bossoroca Complex, São Gabriel Terrane, Dom Feliciano Belt, southernmost Brazil: UPb geochronology and tectonic implications for the neoproterozoic São Gabriel Arc. (October 2016) - Gubert, Mauricio Lemos; Philipp, Ruy Paulo; Stipp Basei, Miguel Angelo
Abstract: UPb LA-ICPMS geochronological analyses were carried out on zircon grains from metavolcanic rocks of the Bossoroca Complex and for one ash tuff of the Acampamento Velho Formation of the Camaquã Basin, in order to understand the evolution of the Neoproterozoic São Gabriel magmatic arc. A total of 42 analyses of igneous zircon grains were performed in three samples. The results yielded UPb ages of 767.2 ± 2.9 Ma for the metavolcanic agglomerate (BOS-02); 765 ± 10 Ma for the metacrystal tuff (BOS-03) and 565.8 ± 4.8 Ma for the ash tuff (BOS-04). The Orogenic Cycle in Brazil is characterized by a set of orogenic belts consisting of petrotectonic associations juxtaposed by two collisional events that occurred at the end of the Neoproterozoic. In southern Brazil this orogeny formed the Dom Feliciano Belt, a unit composed of associations of rocks developed during two major orogenic events called São Gabriel (900–680 Ma) and Dom Feliciano (650–540 Ma). The main São Gabriel associations are tectonically juxtaposed as elongated strips according to the N20–30°E direction, bounded by ductile shear zones. The Bossoroca Complex comprises predominantly metavolcano-sedimentary rocks, characterized by medium-K calc-alkaline association generated in a cordillera-type magmatic arc. The volcanism occurred in sub-aerial environment, developing deposits generated by flow, resurgence and fall, sporadically interrupted by subaqueous epiclastic deposits, suggesting an arc related basin. The São Gabriel Terrane contains the petrotectonic units that represent the closure of the Charrua Ocean associated to the subduction period of the Brasiliano Orogenic Cycle in the Sul-rio-grandense Shield. Highlights: New stratigraphic, petrographic and UPb geochronological data on igneous crystallization of the Bossoroca Complex. Investigated the metamorphic conditions of the Bossoroca Complex and original conditions of metavolcanic rocks deposition. The UPb zircon determinations demonstrated that the metacrystal tuffs and meta-agglomerates exposed in the Bossoroca crystallized between 765 ± 10 Ma and 767.2 ± 2.9 Ma.